Is there evidence for the added value and correct use of manual and automatically switching multimemory hearing devices? A scoping review. (4th March 2018) - de Graaff, Feike; Huysmans, Elke; Ket, Johannes C.F.; Merkus, Paul; Goverts, S. Theo; Leemans, C. René; Smits, Cas
Abstract: Objectives : To review literature on the use of manual and automatically switching multimemory devices by hearing aid and CI recipients, and to investigate if recipients appreciate and adequately use the ability to switch between programmes in various listening environments. Design : Literature was searched using PubMed, Embase and ISI/Web of Science. Additional studies were identified by screening reference and citation lists, and by contacting experts. Study sample : The search yielded 1109 records that were screened on title and abstract. This resulted in the full-text assessment of 37 articles. Results : Sixteen articles reported on the use of multiple programmes for various listening environments, three articles reported on the use of an automatic switching mode. All studies reported on hearing aid recipients only, no study with CI recipients fulfilled the selection criteria. Conclusions : Despite the high number of manual and automatically switching multimemory devices sold each year, there are remarkably few studies about the use of multiple programmes or automatic switching modes for various listening environments. No studies were found that examined the accuracy of the use of programmes for specific listening environments. An automatic switching device might be a solution if recipients are not able, or willing, to switch manually between programmes.